Cardiac evaluation of Covid-19 patients with post-discharge dyspnoea - Dr. Sibaram Panda; Dr. Sunil Kumar Sharma (International Journal of Medical Research and Review, 2020)
Background: Dyspnoea is one of the common symptoms in COVID-19 patients after discharge from the hospital. So evaluation of cardiac function becomes necessary in COVID patients after hospital discharge.AIM: To study the cardiac function of COVID 19 patients presenting with dyspnoea after discharge from hospital within 3 months of symptom onset.Materials and methods: 245 post-hospital discharge COVID-19 patients enrolled in the study. The patients with abnormal echocardiography are further divided into three groups, A) patients with PAH±RVD, B) patients with LV diastolic dysfunction C) patients with LV systolic dysfunction. Data of the three groups were compared.Results: Out of 245 patients, 64% (157) patients show abnormal echocardiogram.75 (30.6%) patient show PAH±RVD,61(24.8% ) patients shows LV diastolic dysfunction and 21(8.57%) patients shows LV systolic dysfunction. patients with ventricular dysfunction significantly associated with multiple risk factors and comorbidity. Grade 1,2,3,4 diastolic dysfunction seen in 27.8%,34.4%,29.5%,8.1% in group B respectively. LV systolic dysfunction is mild in 13 (61.9%), moderate in6(28.5%), severe in 1 (4.7 %) in group C patients. Ntprobnp, tropnin significantly higher in all groups. Also, CRP, D dimer significantly higher in group A, but non significantly higher in group B, C.Conclusion: RV dysfunction is the most common pattern seen in around 30% of patients. LV diastolic dysfunction is not uncommon, seen in ¼ the patients. Patients with cardiac dysfunction have a high level of cardiac and inflammatory biomarkers, which can lead to grievous cardiovascular complications. So close follow up required.